Греческая колонизация Леванта: Этнические и социокультурные контакты эпохи архаики - Согомонов, А. Ю.
Sogomonov, A. Ju., Greek Settlements in the Near East and their Ethno-Cultural Contacts in the Archaic Period; ab 8. Jh. v. Chr.